The Effect of Rupiah Exchange Rate, Firm Size, Leverage and Liquidity on Hedging Decision Making Using Derivative Instruments - Tunggu Ariana; Vina Marlisa (International Journal of Social Service and Research, 2021)
Companies facing the risk of fluctuations in foreign exchange rates can hedge with derivative instruments such as forward, future, swap and option contracts. The purpose of this study was to determine the effect of exchange rates, firm size, leverage and liquidity on hedging decision making using derivative instruments in BUMN companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The method of determining the sample using purpose sampling technique and obtained 12 samples that meet the criteria and 144 firm-quarter observation. The analysis technique used is descriptive statistics and logistic regression. The test results show that the rupiah exchange rate has positive no significant effect on hedging decision making using derivative instruments. Firm size variable has a positive significant effect on hedging decision making using derivative instruments. The leverage variable which is proxied by debt to ratio has a negative significant effect on hedging decision making using derivative instruments. Liquidity which is proxied by current ratio has a negative significant effect on hedging decision making using derivative instruments